PENGARUH SUHU PENGERINGAN TERHADAP KARAKTERISTIK TEPUNG LABU KUNING (Cucurbitae Moschata ex. Poir) BESERTA ANALISIS FINANSIALNYA - Gria Mas Arum, IGA Dharmapadni; Admadi H, Bambang; Sedana Yoga, I Wayan Gede (JURNAL REKAYASA DAN MANAJEMEN AGROINDUSTRI; Vol 4 No 2 (2016): Juni)
This study aims to 1) Determine the effect of drying temperature on the characteristics of pumpkin flour 2) Determine the best temperature to produce the best characteristics pumpkin flour 3) Determine the financial feasibility of flour pumpkin. This research is designed using a laboratory scale randomized block design with treatments that drying temperature (50, 60, 70, and 80) ?C and 3 grouping processing time. The best treatment is determined by the effectiveness of the test, followed by analysis of financial. The resut showeds that drying temperature of the flour pumpkin had very significant effect on yield, water content, ash content, protein content, fat content, carbohydrate content and levels of beta carotene. Pumpkin flour best treatment is temperature 60?C with characteristics: yield of 22.00%, 14.51% water content, ash content of 5.79%, 1.07% protein content, and fat content 1.19%, carbohydrate content 82.02% and beta carotene levels of 2295.81 g / 100g. Pumpkin flour production costs with the best treatment Rp.166.780.400 a year and price was Rp.41.063/ kg, Break Event Point analysis of 2.241,77 kg a year, Return on Investment of 35.06%, and Pay Back Period of 2,85 years so it is feasible to run the bussines. Keywords: characteristics, drying temperature, flour pumpkin
Keywords: 99,